2018
DOI: 10.4064/cm7027-12-2016
|View full text |Cite
|
Sign up to set email alerts
|

On the uniform convergence of double sine series

Abstract: The fundamental theorem in the theory of the uniform convergence of sine series is due to Chaundy and Jolliffe from 1916 (see [1]). Several authors gave conditions for this problem supposing that coefficients are monotone, non-negative or more recently, general monotone (see [8], [6] and [2], for example). There are also results for the regular convergence of double sine series to by uniform in case the coefficients are monotone or general monotone double sequences. In this article we give new sufficient condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Duzinkiewicz and Szal [7] introduce a new class of double sequence called ( , , , ), which is a generalization of the class considered by Kórus, and they obtain sufficient and necessary conditions for uniform convergence of double sine series.…”
Section: Theorem 4 Was Generalized Bymentioning
confidence: 99%
“…Duzinkiewicz and Szal [7] introduce a new class of double sequence called ( , , , ), which is a generalization of the class considered by Kórus, and they obtain sufficient and necessary conditions for uniform convergence of double sine series.…”
Section: Theorem 4 Was Generalized Bymentioning
confidence: 99%
“…Duzinkiewicz and Szal [2] introduce a new class of double sequences called DGMðα, β, γ, rÞ, which is a generalization of the class considered by Kórus, and they obtain sufficient and necessary conditions for uniform convergence of double sine series.…”
Section: Introductionmentioning
confidence: 99%
“…
We introduce a new class of double sequences called DGM (p, α, β, γ, r), which is a generalization of a class considered by Duzinkiewicz and Szal (2018). We obtain a necessary condition for the uniform convergence of double sine series with coefficients belonging to this class.
…”
mentioning
confidence: 99%
“…He also showed that MVBVDS SBVDS 1 . Next, Duzinkiewicz and Szal [2] defined a new class of sequences: Definition 1.7. A double sequence c := {c jk } ∞ j,k=1 ⊂ C belongs to DGM(α, β, γ, r) (called Double General Monotone), if there exist a positive constant C and an integer λ ≥ 1, depending only on (c jk ) ∞ j,k=1 , for which…”
mentioning
confidence: 99%